How to Improve the YLS/CMI? Exploring a Particularly Predictive Combination of Items - Villanueva, Lidón (International journal of offender therapy and comparative criminology, 2019)
Recidivism risk assessment is central to addressing criminogenic needs among youth offenders. To accomplish this, the Youth Level of Service/Case Management Inventory (YLS/CMI) is worldwide used, but it is long and has limited predictive validity for minority populations. This study presents a particularly predictive combination of seven items that overcomes these limitations. A sample of 430 Spanish youth offenders participated in this study. The YLS/CMI long version was filled out and reconvictions were collected over a 2-year period. Results show that this combination of seven items reduced more than 80% of the inventory and improved the predictive validity, globally and for minorities. The items that were included were related to psychopathic traits and the lack of protective role models. Therefore, this specific combination of YLS/CMI items has considerable higher predictive validity across gender and culture, and may be useful to practitioners in this field.